PENGARUH CSR, KINERJA LINGKUNGAN, DAN BIAYA LINGKUNGAN TERHADAP PROFITABILITAS: Studi Empiris Perusahaan Industri Dasar Dan Bahan Kimia - Azizah, Nur; Cahyaningtyas, Fadilla (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
This study aims to examine and analyze the effect of CSR, environmental performance, environmental costs on profitability. The research population is basic industrial sector entities and chemicals for the period 2016 – 2021. The non-probability sampling technique uses a purposive sampling method. The research sample is 7 companies. The results of hypothesis testing show that CSR, environmental performance, and environmental costs have no effect on profitability. This study has theoretical implications in the field of financial accounting, namely obtaining evidence that CSR disclosure, environmental performance, and environmental costs do not affect the size of the profitability of the company. This research also has practical implications, namely that it can be taken into consideration by companies in making decisions, especially to increase profitability, companies must balance the company's focus on increasing sales or on company expenses for CSR disclosure costs, environmental performance, and environmental costs.